Solar energy on Swedish pig farms : a sunny story? - Ekman, Louise; Jonsson, Emelie (SLU/Dept. of Economics, 2014)
In Sweden there is a large interest in renewable energy but the market for solar power is still small compared to other countries such as Germany. Here many farmers produce their own electricity. The Federation of Swedish farmers have acknowledged the potential for Swedish farmer to produce electricity and there is an interest among the farmers. The agricultural branches in Sweden most suitable for solar power are pig production and poultry due to the even electricity need throughout a year. Swedish pig farmers are going through a period of unsteady profitability which makes it interesting to see whether producing their own electricity can affect the economic situation. Earlier studies have shown that it is not profitable on farms to make such investments but due to market developments and rapid changes another study is highly relevant. This thesis’ aim is therefore to see with the help of mathematical modelling; if an investment in a photovoltaic system is economically feasible at a Swedish pig farm, if an investment can affect the profitability of the farm, how sensitive it is and what capacity of a photovoltaic system that is optimal. To reach the aim this study is conducted in a quantitative manner through the use of mathematical programing. A fictive farm has been created through statistics to use in an optimization model comparing eleven different investment options. A sensitivity analysis is also carried out in order to test how changes in different factors affect the outcome of the optimization. Results show that in order for an investment in solar power to be economically feasible on a Swedish pig farm, with the conditions available at time of writing this thesis, there is a need for receiving investment grants and being able to trade electricity certificates. If these basic conditions are met an investment based on the electricity need of the farm is a part of the optimal solution. Another conclusion is that the optimal system size highly depends on the electricity need of the farm.